Model dan Gaya Kepemimpinan Masa Kini - Wasis Suseno (Jurnal Missio Cristo, 2021)
Abstract: The main problem in leadership, the lack of understanding how to lead, so when the leader is not ready to lead, for that in this paper will be discussed how to understand the style & model of leadership is right, so as to understand lead the situation and condition context. The emphasis of this article, on the Model & style of leadership in the present. In the lead of each person has a tendency to have a particular model, there are four models, namely: Catalisator, Commander, Thruster & Hermit, every leader takes one of style, but can combine one or two styles, but certainly every leader has one dominant of the four existing styles. In addition there are for styles, there are still other factors that affect leadership within a person in leadership in the present, Situational leadership style, where a leader is able & sangup to see the condition of the organization he leads, as well as the people he leads, so as to manage with & manage both well.